Holocene, ARC-volcanism controlled, episodic sedimentation in the Atlantic lowland of Costa Rica - Ruitenbeek, F. van (CATIE, Turrialba (Costa Rica). Atlantic Zone Programme Agricultural University Wageningen, Wageningen (Países Bajos) Ministerio de Agricultura y Ganadería, San José (Costa Rica), 2014)
Ilus. Tab. Sum. (En). También como: Field Report - Atlantic Zone Programme (CATIE) no. 120